Motor and cognitive abilities of children born before term - Smudja, Mirjana; Stojanovic Jovanovic, Biljana; Jovanovic, Stevan (PONS - medicinski časopis, 2020)
ABSTRACT With the development of modern perinatal medicine and medical technology, the survival rate of premature infants has increased. However, premature birth is a risk factor for developmental delays. This paper evaluates the available literature to look at dominant developmental domains that reflect dysfunction of pre-term children. Studies in which the subject of the study was to monitor the development of premature infants confirmed a lag in motor and cognitive development, and their interrelation. These results can be explained by: the early negative and unpleasant sensory experiences to which the immature nervous system was exposed ahead of time and the lack of adequate interaction of biological and environmental factors. Even after the prematurity has stabilized and with environmental stimuli that accelerate overall biological processes, many developments have been delayed. The first domain to identify developmental delays in preterm infants is motor development. Studies show that babies born before 32 gestational weeks very often show persistent delays in motor development (gross and fine motor skills, perceptual-motor skills). Another domain that identifies developmental delays in premature infants is cognitive development. Empirical studies reveal that children under 26 weeks of gestational maturity show deficits or developmental delays in maintaining attention during the toddler period. Also, in these children, during the adolescence period, lower capacities of active and passive visual-spatial working memory were observed, which influences the acquisition of knowledge in mathematics, as well as the general achievement in school. Keywords: Preterm; Extremely preterm children; Motor development; Cognitive development; General movement.